Cardiovascular effects of total soyasaponin in central nervous system and its relationship with monoamine transmitters - Guo Jian-Hui; Tang Yu-Huan; Wei Yong-Di; Li Jian-Hua; Zhao Hua; Wang Shao (Acta Pharmacologica Sinica, 2016)
AIM: To study the cardiovascular effect of total soyabeans saponins (TS) in brain and its relationship with monoamines. METHODS: After injection of TS (75 micrograms) into ventriculus lateralis cerebri (VLC) the changes of blood pressure (BP) and heart rate (HR) were observed and the contents of monoamines both in peripheral blood and brain (telencephalon, diencephalon, brainstem) were measured respectively by HPLC-ECD and fluorophotometry. RESULTS: After injection of TS into VLC, BP rise from 11.59 +/- 0.84 to 14.59 +/- 0.69 kPa; HR increased from 411 +/- 21 to 465 +/- 14 bpm; the contents of NE and E in peripheral blood increased from 6 +/- 3 to 64 +/- 44, from 6 +/- 2 to 38 +/- 34 nmol/L plasma, respectively, NE in brainstem increased from 14 +/- 0 to 18 +/- 3 nmol/g wet tissue respectively, but the contents of 5-HT in the 3 areas measured in the experiment decreased: in telecephalon from 9 +/- 1 to 5 +/- 1, in diencephalon from 14 +/- 2 to 7 +/- 2, in brainstem from 14 +/- 3 to 6 +/- 1 nmol/g wet tissue. CONCLUSIONS: The cardiovascular effects of TS in CNS were involved in the monoamine transmitters.